Antimicrobial activity of alexidine alone and associated with N-acetylcysteine against Enterococcus faecalis biofilm - Silveira, Luiz Fernando Machado (Nature Publishing Group, 2013)
The purpose of this study was to assess the efficacy of alexidine (ALX), alone and combined with N-acetylcysteine (NAC), in eradicating two Enterococcus faecalis strain biofilms. The biofilms of E. faecalis ATCC 29212 and the clinical isolate E. faecalis D1 were grown in the MBEC-high-throughput device for 24 h and were exposed to five twofold dilutions of ALX (2%–0.007 8%) alone and combined with 100 mg⋅mL(−1) NAC, for 1 and 5 min. Eradication was defined as 100% kill of biofilm bacteria. The Student's t-test was used to compare the efficacy of the associations of the two irrigants. After 1-min contact time, ALX eradicated the biofilms at all concentrations except for 0.007 8% and 0.015 6%–0.007 8% with E. faecalis ATCC 29212 and E. faecalis D1, respectively. Similar results for eradication and concentration were obtained when it was combined with 100 mg⋅mL(−1) NAC. After 5 min of contact time, ALX alone and combined with NAC eradicated all enterococci biofilms. ALX showed antimicrobial properties against the two E. faecalis strain biofilms tested at very low concentrations, and its combined use with NAC was not seen to enhance its activity.